Learning From Calypso - Herbert, Susan (Daily Express, 2003)
This article reflects on one of the controversies of the 2003 calyspo season in Trinidad and Tobago with respect to double entendre calypsoes, and relates it to the issue of classroom communication, as well as to self-esteem with respect to national culture. It concludes with the suggestion that calypsoes might be able to teach us a great deal that we can apply to the formal education system, while learning something about ourselves in the process
Keywords: Calypsoes; Classroom communication; Self concept; Education and culture; Trinidad and Tobago